Seventeenth-century women's dress patterns book one - North, Susan; Robins, Paul.; Tiramani, Jenny; Davis, Richard (London V & A Publications, 2011)
This breathtakingly detailed book presents dress patterns, construction details, embroidery and making instructions for fifteen garments and accessories from a seventeenth-century woman's wardrobe. Full step-by-step drawings of the construction sequence are given for each garment alongside photographs of the objects and x-ray photography.
The tools and techniques of the tailor and seamstress -- Embroidery tools and techniques -- Knitting stitches -- Sewing stitches -- Embroidery stitches -- How to use this book -- Margaret Layton's waistcoat, 1610-15 / Claire Thornton -- Pink silk waistcoat, 1610-20 / Jenny Tiramani -- Blackwork waistcoast, 1620-25 / Luca Costigliolo -- Fustian waistcoast, 1630s / Jenny Tiramani -- Slashed satin bodice, 1630s / Luca Costigliolo -- Knitted silk waistcoat, 1630-1700 / Susan North -- Embroidered linen mantle, 1590-1610 / Claire Thormton -- Linen smock, 1620-40 / Armelle Lucas -- Linen hood, 1600-1640 / Armelle Lucas -- Embroidered coif and forehead cloth, 1600-1650 / Armelle Lucas -- Linen band and cuffs, 1630-35 / Jenny Tiramani -- Embroidered partlet and sleeve panels, 1615-25 / Jenny Tiramani -- Linen kerchief, 1600s / Susan North -- Embroidered linen gloves, 1600-1625 / Claire Thornton -- Embroidered kid gloves, 1610-30 / Jenny Tiramani
Book one edited by Susan North and Jenny Tiramani.
Keywords: Clothing and dress -- History -- 17th Century; Dress accessories -- History -- 17th Century; Fashion -- History -- 17th Century